Perceived Organizational Support Terhadap Komitmen Organisasi dan Kinerja Karyawan - Anggita Rinda Pratiwi; Muzakki muzakki Muzakki (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
PT. Panca Mitra Multi Perdana is a company engaged in the export-import field. The production division is a division with a large workload and generally has the highest employee turnover compared to other divisions. Employee turnover can be suppressed by increasing perceived organizational support. This is because perceived good organizational support is directly proportional to organizational commitment and employee performance. This study aims to determine the effect of perceived organizational support on organizational commitment and employee performance on production division employees at PT. Panca Mitra Multi Perdana, located in Situbondo. This research uses causal quantitative research. The sample in this study amounted to 100 employees of the production division at PT. Panca Mitra Multi Perdana, located in Situbondo. Samples were selected using the purposive sampling method. Research data were analyzed using the Partial Least Square (PLS) method. The results showed that perceived organizational support had a positive and significant effect on organizational commitment with an R-Square value of 0.9123 (91.23%). Perceived organizational support has a positive and significant effect on employee performance with an R-Square value of 0.8997 (89.97%).